Delay in breast cancer diagnosis - Gateño, Nisso; Borges, Freddy; Favat, Juan; Ramos, Sergio; Priario, Julio César (Cirugía del Uruguay, 1972)
In 502 case records of mammary carcinoma treated at the. clinics Hospital of Montevideo, it was observed that 67 % of these cases were in advanced stages at the time of the first consultation, In 12 % of those advanced cases the responsability was due to the physician. Stress is placed on the importance of routine examination of mammary glands as well as a better medical and sanitary education as an answer to the problem,